The normalized signless laplacian estrada index of graphs - Ş. Burcu Bozkurt Altındağ; Emina Milovanovic; Marjan Matejic; Igor Milovanovic (Transactions on Combinatorics, 2023)
Let $G$ be a simple connected graph of order $n$ with $m$ edges. Denote by $% γ _{1}^{+}≥ γ _{2}^{+}≥ … ≥ γ _{n}^{+}≥ 0$ the normalized signless Laplacian eigenvalues of $G$. In this work, we define the normalized signless Laplacian Estrada index of $G$ as $NSEE\left(G\right) =\sum_{i=1}^{n}e^{γ _{i}^{+}}.$ Some lower bounds on $%NSEE\left( G\right) $ are also established.